The Influence of Hypercontent-Based Joyful Learning Strategy on Student Learning Effectiveness in Islamic Religious Education Subjects - Hani Nurulhanifah; Yufi Mohammad Nasrullah; Anton, Anton (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the effect of the Hypercontent-based Joyful Learning strategy on students’ learning effectiveness in Islamic Religious Education (IRE) at SMA Negeri 1 Garut. This research employed a descriptive quantitative approach with simple linear regression analysis. The research population consisted of all eleventh-grade students totaling 350 students, with a sample of 75 students determined using the Slovin formula and stratified random sampling technique. Data were collected through observation, interviews, questionnaires, and documentation. Instrument validity was tested using Pearson Product Moment correlation, while reliability was tested using Cronbach’s Alpha with a value of 0.730, indicating that the instrument was reliable. Data processing and analysis were conducted using the Statistical Package for the Social Sciences (SPSS) software. The results showed that the Hypercontent-based Joyful Learning strategy had a significant effect on students’ learning effectiveness, with a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) value of 0.535 indicates that the Hypercontent-based Joyful Learning strategy contributed 53.5% to students’ learning effectiveness, while the remaining 46.5% was influenced by other factors outside this study. The contribution of this study lies in presenting empirical evidence regarding the implementation of the Hypercontent-based Joyful Learning strategy in Islamic Religious Education at the secondary school level, which has been rarely examined in previous studies. Furthermore, this study provides empirical evidence on the integration of innovative digital technology–based learning strategies in Islamic Religious Education (PAI) to enhance students’ learning effectiveness at the secondary school level. The findings also strengthen the development of innovative learning strategies that integrate digital technology with the characteristics and objectives of Islamic Religious Education to improve students’ learning effectiveness.